2009
DOI: 10.1556/aoecon.59.2009.4.4
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between education and country-risk: A new fact

Abstract: The relationship between education and country-risk is an almost neglected question in economic literature, despite the several reasons for which these two issues could be related. In a recent article by Sequeira — Ferraz (2009) a linear relationship is documented. The present article provides evidence that the strength of the relationship between country-risk and education decreases for higher levels of GDP. It also proves that this decrease consistently applies for secondary and tertiary education levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Hanushek and Woessmann (2011) concluded that there is very little evidence in support of the influence of inputs in cross-country differences in schooling achievements while recognizing the essential effects of family and social background and of some countryspecific school-related institutions. For example, Sequeira and Ferraz (2009) and Sequeira (2009) highlight the significant effect that country-risk has in education measures, and Galor and Klemp (2014) analyse the biocultural origins of human capital formation, using an extensive genealogical record for nearly half a million individuals in Quebec from the 16 th to the 18 th century, highlighting the importance of the choice toward child quality in the process of evolution of human capital through history.…”
Section: Introductionmentioning
confidence: 99%
“…Hanushek and Woessmann (2011) concluded that there is very little evidence in support of the influence of inputs in cross-country differences in schooling achievements while recognizing the essential effects of family and social background and of some countryspecific school-related institutions. For example, Sequeira and Ferraz (2009) and Sequeira (2009) highlight the significant effect that country-risk has in education measures, and Galor and Klemp (2014) analyse the biocultural origins of human capital formation, using an extensive genealogical record for nearly half a million individuals in Quebec from the 16 th to the 18 th century, highlighting the importance of the choice toward child quality in the process of evolution of human capital through history.…”
Section: Introductionmentioning
confidence: 99%